Metallofullerenes: a new class of MRI agents and more?. (November 2013) - Fatouros, Panos P; Shultz, Michael D
Metallofullerenes have incited research endeavors across many disciplines owing to their wide range of properties obtainable by altering the metal component inside the fullerene cage or by a variety of surface functionalities. With a metal component of gadolinium, gadofullerenes have particularly shown promise in MRI applications owing to their high proton relaxivity and isolation of the metal from the biological environment. This article aims to give a perspective on the development of metallofullerenes as MRI contrast agents and further applications that distinguish them as a new class of imaging agent.